AN EFFICIENT SPECTRUM SENSING TECHNIQUE ANALYSIS FOR ADHOC WIRELESS COOPERATIVE COGNITIVE RADIO NETWORKS - Dr. G.K.D. Prasanna Venkatesan, Dr. A.Sridevi (International Journal of Advanced Science and Technology, 2020)
The under utilization problem of the spectrum is overcame by the new standard called as cognitive radio. In cognitive radio the primary function is spectrum sensing. There are several algorithms involved in spectrum sensing under cooperative detection process, among which Adaptive double energy detection and Matched filter are easily implemented. The performance of conventional energy detector and matched filter weakens on lower SNR region. The proposed algorithm of double threshold Energy detection and Dynamic Matched filter detection method of sensing produces better performance than the conventional methods. This double threshold Energy detection and Dynamic matched filter detection using various modulation schemes BPSK and DQPSK. The Dynamic matched filter technique of sensing provides exact sensing than double threshold Energy detection.